Workplace interventions to prevent musculoskeletal and visual symptoms and disorders among computer users: a systematic review. - Brewer S; Van Eerd D; Amick BC III; Irvin E; Daum KM; Gerr F; Moore JS; Cullen K; Rempel D (Journal of Occupational Rehabilitation, 2006)
Background: The literature examining the effects of workstation, eyewear and behavioral interventions on musculoskeletal and visual symptoms among computer users is large and heterogeneous. Methods: A systematic review of the literature used a best evidence synthesis approach to address the general question 'Do office interventions among computer users have an effect on musculoskeletal or visual health?' This was followed by an evaluation of specific interventions. Results: The initial search identified 7313 articles which were reduced to 31 studies based on content and quality. Overall, a mixed level of evidence was observed for the general question. Moderate evidence was observed for: (1) no effect of workstation adjustment, (2) no effect of rest breaks and exercise and (3) positive effect of alternative pointing devices. For all other interventions mixed or insufficient evidence of effect was observed. Conclusion: Few high quality studies were found that examined the effects of interventions in the office on musculoskeletal or visual health.